Pengaruh Karakteristik Sasaran Penganggaran Terhadap Kinerja Manajerial Pada Pemerintah Kabupaten Polewali Mandar Provinsi Sulawesi Barat - Muhammad Sarjan (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2013)
The objective of this Research is to be know the effect of budgeting goal characteristics namely; budgetary goal participation, budgetary goal clarity, budgetary goal difficulty, and budgetary feedback on the manajerial's performance on commanding Regency Polewali Mandar Western Sulawesi. The location of research is regency Polewali Mandar by takes sample 29 SKPD’S managers and 29 SKPD’S finance department managers of as much 57 SKPD .The Sample was selected using purpose sampling method. And data is analysed by using the Linear Regression. Based on the respons of 55 respondent, the result of this research shows that budgetary goal participation, budgetary goal Clarity, and budgetary feedback, have positive and signifikan effect on manajerial's performance. The goal difficulty budgetary has negative insign and significant on managerial performance. The result of this research generally indicates thet hight managerial level can improved the middle managerial performance on Commanding Regency Polewali Mandar with strive budgetary goal participation, budgetary goal Clarity, budgetary goal difficulty and budgetary feedback to managerial performance.